(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This essay would be an introduction to some unpublished works coming from the personal archive of Claudio Meldolesi and based on the Italian theatrical direction, a contradictory matter. In one unwritten work, Meldolesi focuses on the Italian actor role from the Commedia dell’Arte decline up to the rise of the “pre-direction” phenomena. From the end of the Nineteenth and the beginning of the Twentieth, Eleonora Duse stands out from the other protagonists of the Italian scenic art. The actress, in fact, is close to the main poets and artists of that period, among them Gabriele D’Annunzio, with whom she collaborates. The “pre-direction” is not outdated, otherwise, it is possible to find out something similar in many Nineteenth art successors. Some of them, as De Bernardinis, Fabbri and Ronconi, are recently passed away, others instead, are still alive, fortunately, as Carlo Cecchi.